Exophiala dermatitidis, ‘the real black fungus’ fungemia in a patient with COVID-19 - Tzar, Mohd Nizam; Meor Jamaludin, Wan Husna Barakah; Abdul Wahab, Asrul; Chuan, Hun Ding (Elsevier Ltd., 2022)
The second wave of the COVID-19 pandemic in India had brought with it a surge of ‘black fungus’ co- infection, which is a misnomer for mucormycosis. The present case illustrates the ‘real black fungus’ infection in a 50-year old male patient with COVID-19 pneumonia, who otherwise had no significant previous medical history. He was admitted on day 8 of COVID-19 illness and was intubated due to persistently low oxygen saturation. Blood cultures were positive for flask-shaped dematiaceous budding yeasts with pseudohyphae formation, which grew as brown-black fuzzy colonies on Sabouraud dextrose agar. The isolate was identified as Exophiala dermatitidis based on phenotypic characterization. Despite antifungal therapy with amphotericin B and itraconazole, the patient deteriorated rapidly and succumbed to acute respiratory distress syndrome and multiorgan failure. A review of reported cases of Exophiala dermatitidis fungemia over the last 5-years is discussed.